Infecciones profundas del cuello - Jiménez Y., Rodrigo; Rappoport W., Daniel; Ramírez, Enrica; Gac E., Patricio; Rodríguez M., Francisco; Cabané T., Patricio (Revista Hospital Clínico Universidad de Chile, 2019)
Deep neck infections (DNIs) are special entities among infectious diseases for their versatilityand potential for severe complications. Complex head and neck anatomy often makes earlyrecognition of DNIs challenging, and a high index of suspicion is necessary to avoid any delay intreatment. The diagnosis is made by clinical history, physical examination findings and imagingstudies. The treatment consists in securing the airway, intravenous antibiotics and surgicaldrainage, when needed. To make decisions the surgeon must understand the anatomy ofthe region, the etiology of infection, appropriate diagnostic tools, and medical and surgicalmanagement. This article provides a review of these pertinent topics.